Evidence Based Case Report: Penggunaan Metode PCR Pada Sputum Untuk Diagnosis Pulmonary Aspergillosis - Augustine Natasha; Ricky Fernando; Tubagus M. Kurniadi; Elyn Dohar Idarin Aritonang; Angky Budianti (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2019)
Background: Pulmonary Aspergillosis is an opportunistic infection in the immunocompromised population. The polymerase chain reaction (PCR) method is expected to be a substitute for sputum mushroom culture with faster and more accurate results. Method: Searched in PubMed, CENTRAL, EbscoHost, and ProQuest from October 1-13 using the keywords “Aspergillosis”, “Pulmonary Aspergillosis”, “sputum”, “PCR”, “sputum fungal culture”. The search results are evaluated using inclusion and exclusion criteria. The selected study is then obtained by the full text and re-evaluated. The final results of the selection were then critically reviewed by validity, importance, and applicability by the three authors. Results: Four studies were obtained, with level of evidence 4, which were then critically reviewed. Three studies used PCR in sputum samples as index tests, while one study used it as a reference test. Output from three studies reported sensitivity and specificity of PCR with sputum samples, while one study reported a proportion of PCR results. Two studies reported PCR sensitivity in sputum samples of 100%, while one study reported a sensitivity of 38%. Two studies also reported specificities above 70%, while one study reported a specificity of 38.5%. Conclusion: Studies show promising values of sensitivity and specificity, especially with results obtained quickly. However, the low level of evidence and its costs are quite expensive, causing detection by the PCR method that cannot be used as a routine diagnostic modality.